Gerakan Ekonomi Islam Konservatif-Politik, Wajah Konstruktivisme Kewirausahaan Komunitas Hijrah Indonesia - Aang Kunaifi; Burhan Djamaluddin; Ika Yunia Fauzia; Iskandar Ritonga; Nurhayati; Nur Syam; Tika Widiastuti; Muhamad Ahsan (IQTISHODUNA: Jurnal Ekonomi Islam, 2025)
One can interpret the hijra community's economic impact in Indonesia as both beneficial and detrimental. The purpose of this paper is to elucidate the typology of the Indonesian Islamic entrepreneurial movement and the hijrah community movement's compromise model for economic rules. Observations at community business locations, interviews with entrepreneurs in 10 communities, documentation in the form of brochures, photos of activities, and information on Facebook, Instagram, and WhatsApp groups were used in the research, which followed a case study methodology. Three of the 22 informants who were thoroughly questioned were expert informants. The regions of origin of the informants included Java, Sumatra, Bali, NTB, Sulawesi, and Kalimantan. To generate fresh hypotheses, data were examined using theoretical PPIM and Carter and Banker's hijra community typology propositions. The study's findings demonstrate the political conservatism of the hijra community's Islamic economic movement. Specifically, the dominant economic system, the Islamic economic movement, aims to replace conventional or ribawi economics, or is portrayed as such in the dual system notion.